Charter to William Penn, And Laws of the Province of Pennsylvania, Passed Between the Years 1682 and 1700, at 32 (1879) - (:unkn) unknown (My University, 1676)
Prohibited the giving, selling, or bartering guns, ammunition, armour, or boats and the repair of guns to "any Indian," punishable by fine.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES